A rare case of rapidly progressive dementia with elevated RT-QuIC and negative 14-3-3 and tau proteins. Issue 3 (3rd May 2016) - Trikamji, Bhavesh; Hamlin, Clive; Baldwin, Kelly J.
ABSTRACT: Creutzfeldt-Jakob disease (CJD) is characterized by rapidly progressing dementia with death usually occurring within 6 months. There is no verified disease-specific pre-mortem diagnostic test besides brain biopsy. We describe a 66 y old previously high functioning male who presented with a 5 month history of rapidly progressive dementia. Neurological examination revealed a score of 19/30 on MOCA testing. An extensive workup into various causes of dementia including electroencephalography and imaging studies was unremarkable. The cerebrospinal fluid was sent to National Prion Disease Center and it revealed elevated RT-QuIC levels with negative 14-3-3 and T tau proteins. Based on literature review, our case is one of few living subjects with elevated RT-QuIC levels and negative 14-3-3 and tau proteins.